Nutrition Care Process in Pediatric Patients with Burn Injury Post Debridement Day 7 - Rahmah, Hiya Alfi; Cempaka, Anggun Rindang (Ikatan Sarjana Gizi Indonesia (ISAGI), 2024)
The condition of burn injury can cause disturbances in the body's metabolism, which can ultimately affect the patient's nutritional status. Therefore, in its management, it requires standard nutritional care processes to improve the condition and meet the nutritional needs of the patient. Nurition Care Process was carried out through four stages: assessment, diagnosis, intervention, and regular monitoring and evaluation. This study aimed to implement nutrition care process (NCP) for burn injury patient during the 3-day intervention period. Case study carried on July 2020 to hospitalized patients of Saiful Anwar Hospital. Observations were implemented for 3 consecutive days. Observations included of 4 steps of NCP, Assessment, Diagnosis, Intervention, Monitoring and Evaluation. After the NCP was carried out, the patient’s condition improves, accompanied by an incrase in food intake